2010
DOI: 10.1111/j.1360-0443.2010.02997.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, suppressed anger and violence

Abstract: Alcohol use may be related causally to violence, but the effect of drinking is confined to individuals who are inclined to suppress their angry feelings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 47 publications
3
41
0
3
Order By: Relevance
“…Similarly, White et al (2013) found that within-person increases in alcohol use lead to increased aggressive behavior among adolescent boys. The impact of alcohol use on aggression and violence may be a function of the temperament among individuals who may display more or less dispositional traits (Norström and Pape 2010) or who live in high-crime neighborhoods (White et al 2013). …”
mentioning
confidence: 99%
“…Similarly, White et al (2013) found that within-person increases in alcohol use lead to increased aggressive behavior among adolescent boys. The impact of alcohol use on aggression and violence may be a function of the temperament among individuals who may display more or less dispositional traits (Norström and Pape 2010) or who live in high-crime neighborhoods (White et al 2013). …”
mentioning
confidence: 99%
“…A causal role for substance abuse in violence has been suggested by findings from prospective studies showing a close association between substance abuse prior to violent acts (Greenfield, 1998;Norstrøm & Pape, 2010). Our correlation design does not allow for the conclusion that multiple substance abuse is a causal factor for violence, although the gradual increase in violence propensity associated with higher numbers of abused substances meets one of the criteria for a causal relationship (Hill, 1965).…”
Section: Discussionmentioning
confidence: 71%
“…Examples of such factors are high levels of suppressed aggression and negative affect, suspiciousness, reduced impulse control, and hampered regulation of stress and emotions (e.g., Nestor, 2002;Norstrøm & Pape, 2010). Other factors include an adverse life history and negative aspects of current life situation, such as physical victimization and living in a high criminality environment, early exposure to substance abuse by parents, and social isolation (Gill-Gonzales et al, 2008;Wei & Brackley, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Norström (19) plantea una hipótesis más selectiva de esta relación; sostiene que solo las personas con una predisposición agresiva y que reprimen sentimientos de ira, frente a la exposición al alcohol aumentan el riesgo de manifestar comportamientos violentos en relación con la sensación de desinhibición que experimentan bajo sus efectos. Según Sahel (20), es importante tener claro que el consumo de alcohol puede conducir a la violencia, pero es igualmente posible que los adolescentes que se dedican a la violencia sean más propensos a buscar el alcohol (tabla 3).…”
Section: Discussionunclassified